Determinan impor Indonesia - Andi Andini Adhalia; Rachmad R; Rahma Nurjanah (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The purpose of this study is to analyze: 1) The development of import values, inflation, exchange rates, FDI, and Indonesia's foreign exchange reserves for the period 1996-2017. 2) The influence of Indonesia's import determinants for the 1996-2017 period. In this study, the type of data used is secondary data based on the period 1996-2017. The method used in this research is descriptive analysis and quantitative analysis, namely multiple regression analysis. The results of this study indicate: 1) The average development of imports is 8.68% per year, the average inflation is 10.30% per year, the average development of the rupiah exchange rate against the dollar is 11.17% per year, the average development FDI is 5.66% per year, and the average development of foreign exchange reserves is 11.83% per year. 2) Simultaneously or together inflation, exchange rate, FDI, and foreign exchange reserves have a positive and significant impact on Indonesian imports. Partially, inflation has a positive and significant effect on Indonesian imports, the exchange rate has a negative and significant effect on Indonesian imports, FDI has a positive but not significant effect on Indonesian imports, and foreign exchange reserves have a positive and significant effect on Indonesian imports. Keywords: Imports, Inflation, Exchange rates, Foreign direct investment, Foreign exchange reserves